Engineering local coordination environments and site densities for high‐performance Fe‐N‐C oxygen reduction reaction electrocatalysis. (1st June 2021) - Wang, Qing; Shang, Lu; Sun‐Waterhouse, Dongxiao; Zhang, Tierui; Waterhouse, Geoffrey
Abstract: Fe‐N‐C catalysts represent very promising cathode catalysts for polymer electrolyte fuel cells, owing to their outstanding activity for the oxygen reduction reaction (ORR), especially in alkaline media. In this review, we summarize recent advances in the design and synthesis of Fe‐N‐C catalysts rich in highly dispersed FeN x active sites. Special emphasis is placed on emerging strategies for tuning the electronic structure of the Fe atoms to enhance the ORR activity, and also maximizing the surface concentration of FeN x sites that are catalytically accessible during ORR. While great progress has been made over the past 5 years in the development of Fe‐N‐C catalyst for ORR, significant technical obstacles still need to be overcome to enable the large‐scale application of Fe‐N‐C materials as cathode catalysts in real‐world fuel cells. Abstract : The advancement of Fe‐N‐C catalysts for oxygen reduction reaction is summarized in two aspects, including (1) discovering advanced FeN x sites with the tuned electronic structure of the Fe atoms to enhance the oxygen reduction reaction (ORR) activity, and (2) developing effective strategies in maximizing the surface concentration of FeN x sites that are catalytically accessible during ORR.